PERANAN PERPUSTAKAAN SEKOLAH DI SMA MUHAMMADIYAH 1 PONTIANAK DALAM MENUNJANG PROSES PEMBELAJARAN - Rini Aprianti; Sisilya Saman Madeten (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis study discusses the role of school libraries in SMA Muhammadiyah 1 Pontianak. The purpose of this study was to determine the extent of the role of the Muhammadiyah 1 Pontianak school library in supporting the learning process in schools both in the provision of collections, as well as ways to overcome various obstacles in the school library that can hinder the learning process. The method used in this research in descriptive with a qualitative appproach that describes the events based on the data obtained. Data collection is done by guiding observation, interviews, and dokumention. The results of this study indicate that the role of the Pontianak Muhammadiyah 1 Library in supporting th learning process in terms of collections of package books is adequate but still needs to be improved, while recreational books such as fiction books are still very minimal so collection is needed. Then some library obstacles that hinder the learning process, one of them is human resources who lack understanding about library management. Keywords : Role, School Library, Learning Process